O efeito das nanopartículas de L-Triptofano e exercício físico no comportamento cognitivo e motor de ratos após indução de placas senis por Beta-Amielóide1-42 - Furmann, Meiriélly (2017)
Introduction: Alzheimer's disease (AD) is a neurodegenerative disorder that causes progressive disability and consequent incapacitation. L-Tryptophan, the precursor of serotonin, regulates important physiological mechanisms, and Nanoparticles, in turn, have the function of increasing the bioavailability of the drugs, enhancing their action. Physical activity in its biological effects may also be related to alteration of cerebral monoamines, such as serotonin, and is beneficial to patients with AD. Materials and methods: The sample consisted of 35 animals, divided into 7 experimental groups (n = 5), being GC- (negative control), GC + (positive control Alzheimer), GNt (exercise), GNtN (exercise + Nanoparticles), GN (Nanoparticles), GLt (L-Tryptophan) and GLtNt (exercise + L-Tryptophan), which received their respective treatments for six consecutive days. Anxiety tests were performed by the cross - labyrinth, spatial memory by the Morris Aquatic Labyrinth, aversive memory by the insulation box aversive test, and motor behavior through the Open Field test, histological analysis. Results: It was observed that in general the L-Tryptophan Nanoparticles presented positive effects in the treatment of AD symptoms, in relation to the cognitive and motor behavior, where there was a decrease in anxiety and improvement of the motor performance by the displacement and exploration of the environment. Acute physical exercise in turn did not present satisfactory results as treatment, although when it was associated with L-Tryptophan, it was shown to be a possible alternative due to the improvement in motor behavior observed through the Size effect analysis, although there is still no a consensus regarding the benefits of exercise for the population with AD, as there are controversies regarding the best type of exercise, intensity and duration necessary to produce the reduction of depressive symptoms. However, further studies are needed to see these possible treatment methods more closely. Conclusion: Even in a short period of treatment, there was an improvement in the symptoms of anxiety and motor behavior (displacement) in which the L-Tryptophan nanoparticles as a treatment method are highlighted.